Peran Kampanye Digital Dalam Pemilu: Partai Solidaritas Indonesia Dalam Pemilu Legislatif 2024 - Silitonga, Novance (Journal Scientific of Mandalika (JSM) e-ISSN 2745-5955 | p-ISSN 2809-0543, 2025)
He Indonesian Solidarity Party’s (PSI) expertise in utilizing the growth and development of internet technology through social media platforms in political campaigns in the 2019 and 2024 elections contributed positively to the national vote. The way PSI coveys ideas in digital campaigns gets the attention of the voting public. As a relatively new political party, PSI must use a digital campaign strategy amid limited resources. This research uses descriptive qualitative research methods. The purpose of the research is to explain the emergence of a symptom in a particular case using certain parameters. By using case studies, researchers explore certain cases or phenomena in detail and in depth with a literature study approach through document searches, journal research and observation in various online news media. Furthermore, the researcher will compile rational and measurable arguments so as to answer the question raised in the research. The results shows that PSI has militancy and consistency with progressive ideas such as anti-corruption, anti-tolerance and gender equality and PSI appears to be the first digital political party in Indonesia.